Transrectal Ultrasound Guided Needle Aspiration of a Prostatic Abscess: Salvage Treatment After Failed Transurethral Resection - David M. Flores; Katie S. Murray; Tomas L. Griebling; Joshua A. Broghammer (Urology Case Reports, 2015)
The treatment for prostate abscesses includes a combination of antimicrobial therapy and surgical drainage of the abscess cavity. There is a lack of published cases involving treatment options for a prostate abscess after a failed transurethral resection of the prostate. This is a case report describing a successful salvage treatment after a failed attempt at abscess drainage by a transurethral resection of the prostate. The patient was successfully managed with a needle drainage of his prostate abscess utilizing a transrectal ultrasound guided needle decompression his prostate abscess.